IB Diploma: Biology for the IB Diploma Workbook with CD-ROM - Matthew Broderick (Cambridge, United Kingdom CAMBRIDGE UNIVERSITY PRESS, 2017)
This workbook is for the IB Biology syllabus, for examination from 2016. Structured chapters build learning in a gradual way, first outlining key terms and then providing students with plenty of practice questions to apply their knowledge. Each chapter concludes with exam-style questions. This approach reinforces learning and builds students' confidence using practical scientific skills such as handling and interpreting data, evaluating information and problem solving. Answers to all of the workbook exercises are on the CD-ROM.
Keywords: IB DP_Group - 4 Biology